2021
DOI: 10.1029/2021ja029645
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Model for Antenna Signal Generation From Dust Impacts

Abstract: Dust impacts on spacecraft are commonly detected by antenna instruments as transient voltage perturbations. The signal waveform is generated by the interaction between the impact‐generated plasma cloud and the elements of the antenna–spacecraft system. A general electrostatic model is presented that includes the two key elements of the interaction, namely the charge recollected from the impact plasma by the spacecraft and the fraction electrons and cations that escape to infinity. The clouds of escaping electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 48 publications
8
48
0
Order By: Relevance
“…Malaspina et al (2022) demonstrated strong connection between the plasma signatures of dust impact ionization and subsequent debris clouds observed by WISPR and the PSP star trackers. This study also demonstrated that long-duration S/C potential perturbations, which follow some dust impacts, are consistent with theoretical expectations for clouds of S/C debris that electrostatically charge in the solar wind (Shen et al 2021a). These perturbations can persist up to 60 seconds, much longer than the brief (µs to ms) voltage spikes generated by the vast majority of dust impacts.…”
Section: Fieldssupporting
confidence: 87%
See 1 more Smart Citation
“…Malaspina et al (2022) demonstrated strong connection between the plasma signatures of dust impact ionization and subsequent debris clouds observed by WISPR and the PSP star trackers. This study also demonstrated that long-duration S/C potential perturbations, which follow some dust impacts, are consistent with theoretical expectations for clouds of S/C debris that electrostatically charge in the solar wind (Shen et al 2021a). These perturbations can persist up to 60 seconds, much longer than the brief (µs to ms) voltage spikes generated by the vast majority of dust impacts.…”
Section: Fieldssupporting
confidence: 87%
“…While there is agreement that electric field sensors detect impact ionization of dust, the physical mechanism by which potential perturbations are generated continues to be an active topic of research, with a range of competing theories (Oberc 1996;Zaslavsky 2015;Kellogg et al 2016;Meyer-Vernet et al 2017;Mann et al 2019;Shen et al 2021b), and rapidly advancing lines of inquiry using controlled laboratory experiments (e.g., Collette et al 2014Collette et al , 2015Collette et al , 2016Nouzák et al 2018;Shen et al 2021a).…”
Section: Fieldsmentioning
confidence: 99%
“…Such a model should include a precise electrostatic description of the spacecraft through a carefully computed elastance matrix that includes all the conductive elements and in particular the antennas, the potential of which was considered as constant in our simplified study. The computation of such an elastance matrix was recently performed by Shen et al (2021) and compared to the results of laboratory experiments of dust impacts on a model spacecraft.…”
Section: More Complicated Model: Taking Additional Effects Into Accountmentioning
confidence: 99%
“…According to the O' Shea et al (2017) numerical analysis, the antennas can only collect charge from impacts that occur in close proximity to the antenna base. Recently, Shen et al (2021) developed a detailed electrostatic model for a generation of antenna signals, applicable to waveforms measured in the laboratory using a dust accelerator, but neglected the plasma effect.…”
Section: Introductionmentioning
confidence: 99%
“…Antenna instruments can register the impacts of cosmic dust particles on spacecraft, as observed by a range of missions [Babic et al, 2022;Gurnett et al, 1983Gurnett et al, , 1987Gurnett et al, , 1997Kurth et al, 2006;Meyer-Vernet et al, 2009, 2017Malaspina et al, 2014Malaspina et al, , 2020Ye et al, 2014Ye et al, , 2016aYe et al, , 2016bYe et al, , 2018Ye et al, , 2019Ye et al, , 2020Kellog et al, 2016;Page et al, 2020;Pusack et al, 2021;Szalay et al, 2020;Vaverka et al, 2018Vaverka et al, , 2019Zaslavsky et al, 2012Zaslavsky et al, , 2015Zaslavsky et al, , 2021. A physical model based on first principles has been recently proposed to interpret and analyze dust impact waveforms recorded by antenna instruments [Shen et al, 2021a;2021b]. In this model, the induced charging (and corresponding potential differences among spacecraft elements) from the expanding cloud of electrons and ions from the impact plasma are primarily responsible for the characteristic shapes of the impact signals.…”
Section: Introductionmentioning
confidence: 99%